Community pharmacist workflow: Space for Pharmacy-based Interventions and Consultation TimE study protocol. (29th April 2020) - Karia, Ajay Mahendrarai; Balane, Christine; Norman, Richard; Robinson, Suzanne; Lehnbom, Elin; Durakovic, Iva; Laba, Tracey-Lea; Joshi, Rohina; Webster, Ruth
Abstract: Background: Pharmacists' roles are expanding to delivering a wider set of professional services including medication management optimisation, vaccinations and screening services. Robust research determining whether pharmacists have the capacity to offer such services in the Australian community pharmacy setting is lacking. This protocol details a mixed methods study that investigates the variation in pharmacists' daily tasks and the workspace they work in as a measure of their workload capacity for expanding pharmacy services. Methods: An observational time and motion study will be conducted in up to twenty community pharmacies in metropolitan and rural regions of Australia. A trained observer will follow a pharmacist and record the type, location and duration of tasks undertaken over the course of their working day. Data will be collected and analysed using the electronic Work Observation Method By Activity Timing (WOMBAT) tool. Pharmacists' work patterns will be described as time for each task, and by proportionating multitasking and interruptions. This information will be combined with workspace data collected using floor plans, photographs and a qualitative assessment of the working environment completed by the observer. Analysis will include heat-mapped floor plans visually highlighting pharmacist movements. Discussion: Pharmacists may provide solutions to the strained health workforce and system. There is limited quantitative evidence on whether pharmacists have the time or work setting to support such needs. The use of time and motion methodology is novel to Australian community pharmacy research, and the findings will provide a better understanding of pharmacists' capacity and work environment.